A novel quantitative trait loci governs prolificacy in 'Sikkim Primitive' – A unique maize (Zea mays) landrace of North‐Eastern Himalaya. (10th May 2021) - Prakash, Nitish R.; Zunjare, Rajkumar U.; Muthusamy, Vignesh; Rai, Mayank; Kumar, Amit; Guleria, Satish K.; Bhatt, Vinay; Choudhary, Jeetram; Chand, Gulab; Jaiswal, Sunil K.; Bhat, Jayant S.; Hossain, Firoz
Abstract: 'Sikkim Primitive' is a prolific maize landrace with five to nine ears per plant. Though the landrace was discovered in 1960s, loci governing the prolificacy was not identified. Here, a prolific inbred 'MGUSP101' developed from 'Sikkim Primitive' was crossed with two nonprolific inbreds, namely, HKI1128 and UMI1200. Two F2:3 populations (MGUSP101 × HKI1128 and MGUSP101 × UMI1200) were evaluated at three locations. Across locations, number of ears per plant varied from 1.35 to 5.38 in MGUSP101 × HKI1128 population. Bulked‐segregant analysis coupled with targeted QTL mapping identified a major QTL (bin: 8.05) explaining 31.7% phenotypic variation amongst 145 F2:3 individuals. The QTL was further validated in 138 F2:3 individuals of MGUSP101 × UMI1200 (range: 1.10–4.88). The identified QTL explained 29.2% of phenotypic variance at the same interval. We designated this novel QTL as ' qProl‐SP‐8 . 05 ' which has not been reported earlier. Six candidate genes responsible for prolificacy were also identified. This novel QTL can be introgressed through marker‐assisted selection for induction of prolificacy in elite maize. This is the first report of identification of locus governing prolificacy in 'Sikkim Primitive'.